Effect of ionic liquids on thermomechanical properties of polyetheretherketone-multiwalled carbon nanotubes nanocomposites - Ahmad, A. (John Wiley and Sons Inc, 2022)
Polyetheretherketone (PEEK) nanocomposites with multiwalled carbon nanotubes (MWCNTs) as a nanofiller have emerged as a potential alternative in biomedical applications. However, the effective dispersion of MWCNTs in PEEK matrices is still challenging due to the low compatibility of the MWCNTs with the polymer phase. This article investigates the effect of two ionic liquids (ILs) at different concentrations on thermomechanical properties of PEEK/MWCNTs composites. MWCNTs are modified with various concentrations (0.5â2Â wt) of ILEMIMAc (1-ethyl-3-methylimidazolium acetate) and ILBMIMHSO4 (1-butyl-3-methylimidazolium hydrogen sulfate), and nanocomposite sheets were prepared by melt-mixing and thermal pressing methods. Optical and field-emission scanning electron microscopy micrographs studies confirmed the homogeneous dispersion of IL-modified MWCNTs in PEEK. Results of nanoindentation and mechanical properties showed the superior mechanical strength of nanocomposites prepared by 1Â wt% IL compared to samples prepared without IL. PEEK/MWCNTs nanocomposites containing 1Â wt% IL provided 37% higher elastic modulus than that of non-IL nanocomposites. ILs based PEEK/MWCNTs nanocomposites exhibited maximum degradation temperature. Thermal degradation kinetics of nanocomposites as modelled by the Coats-Redfern approach indicated the higher activation energy of PEEK/MWCNTs/IL composites. The reported approach for PEEK/MWCNTs nanocomposites fabrication could be potential for promising biomedical applications. Â© 2021 Wiley Periodicals LLC.